“The Country Christ Knew”: New Zealanders' Interactions with Christianity in the Middle East, Greece, and Italy during the Second World War - King, Josh (Journal of religious history, 2023)
During the Second World War, New Zealanders of the Second New Zealand Expeditionary Force (2NZEF) interacted with Christianity throughout the Mediterranean from 1940 to 1945. Stationed in the Middle East, New Zealanders saw the birthplace of Christianity in Egypt and Palestine. In Greece, Crete, and Italy, New Zealanders saw countries where Christianity was deeply ingrained in the landscape and social fabric. This article explores New Zealanders' interaction with Christianity in the Mediterranean during the Second World War on two levels: Firstly, by discussing New Zealanders' visits to Christian religious sites; secondly, by examining New Zealanders' observations on religious practice and the place of religion in society in the Middle East, Greece, and Italy. The article will argue that New Zealanders demonstrated a keen interest in religious tourism during the war, and more broadly, that Christianity was an important lens through which New Zealanders viewed the places in which they served in the Mediterranean.